Penerapan Progressive Muscle Relaxation (PMR) Terhadap Penurunan Tekanan Darah Pada Pasien Hipertensi - Siti Aisah Kudadiri; Armi Mawaddah (STIKES Columbia Asia Medan, 2025)
Hypertension is a condition where blood pressure increases beyond normal limits, with various variations according to age. Various trigger factors cause hypertension, although most (90%) of the causes of hypertension are unknown. The aim of this writing is to be able to understand the concept of hypertension and study nursing care for hypertensive patients as well as to provide the author with an understanding so that he can think logically and scientifically in accordance with the existing reality. The method used was to carry out progressive muscle relaxation therapy for 10 days in 5 visits, namely on 29-07 January 2024. The place for this activity was carried out at the Amplas Community Health Center. Based on the evaluation results, it was found that there was an influence of Progressive Muscle Relaxation therapy to help lowers blood pressure in hypertension patients whose pain scale goes from 6 down to pain scale 3. The conclusion of this paper shows that patients are able to carry out progressive muscle relaxation therapy and can reduce pain in the head and nape of the neck. It is hoped that the results of this research can be used as a medical intervention to reduce acute pain in hypertensive patients in the community.